"Other" behavior and the DRO: The roles of extinction and reinforcement. Issue 4 (7th July 2020) - Hangen, Marcella M.; Romero, Ashley N.; Neidert, Pamela L.; Borrero, John C.
Abstract : Jessel et al. (2015) provided some evidence to suggest that "other" behavior is strengthened in the differential reinforcement of other behavior (DRO). The present study is a systematic replication of the Jessel et al. procedures. The effects of DRO and extinction on target responding, target‐other responding (a response with an established history of reinforcement), and nontarget‐other responding emitted by children with intellectual and developmental disabilities and children with no known diagnoses were compared. Other behavior increased in at least one DRO condition for each participant, suggesting that other behavior increases when using DRO, at least initially. Under extinction, target responding and target‐other responding decreased to low rates for three of the five participants; however, rates of nontarget‐other responding were elevated compared to the DRO condition. These results suggest that increased rates of target‐other responding and nontarget‐other responding during the DRO condition may be a result of extinction‐induced variability.